Targeting Platelets Containing Electro-encapsulated lloprost to Balloon Injured Aorta in Rats - Crawford, N; Chajara, A; Pfliegler, G; Gamal, B EI; Brewer, L; Capron, L (Thrombosis and Haemostasis, 1995)
Drugs can be electro-encapsulated within platelets and targeted to damaged blood vessels by exploiting the platelet’s natural haemostatic properties to adhere to collagen and other vessel wall constituents revealed by injury. A rat aorta balloon angioplasty model has been used to study the effect on platelet deposition of giving iloprost loaded platelets i.v. during the balloon injury. After labelling the circulating platelets with 111-Indium before balloon injury, time course studies showed maximum platelet deposition on the injured aorta occurred at about 1 h post-injury and the deposition remained stable over the next 2-3 h. When iloprost-loaded platelets were given i.v. during injury and the circulating platelet pool labelled with 111-Indium 30 min later, platelet deposition, measured at 2 h postinjury, was substantially and significantly reduced compared with control platelet treatment. Some antiproliferative effects of iloprost-loaded platelets given i.v. during injury have also been observed. Whereas the incorporation of [3H]-thymidine into aorta intima-media DNA at 3 days post injury was 62-fold higher in balloon injured rats than in control sham operated rats, thymidine incorporation into intima/media of rats which had received iloprost loaded platelets during injury was reduced as compared with rats subjected only to the injury procedure. The reduction was only of near significance, however, but at 14 days after injury the total DNA content of the aorta intima/media of rats given iloprost loaded platelets during injury was significantly reduced. Although iloprost loaded platelets can clearly inhibit excessive platelet deposition, other encapsulated agents may have greater anti-proliferative effects. These studies have shown that drug loaded platelets can be targeted to injured arteries, where they may be retained as depots for local release. We believe this novel drug delivery protocol may have therapeutic potential in reducing the incidence of occlusion and restenosis after angioplasty and thrombolysis treatment. Electro-encapsulation of drugs into platelets is a simple procedure and, using autologous and fully biocompatible and biodegradable platelets as delivery vehicles, might overcome some of the immunological and toxicological problems which have been encountered with other delivery vectors such as liposomes, microbeads, synthetic microcapsules and antibodies.